Study of Colombia North Wiwa El Encanto Amerindians HLA- genes: Pacific Islanders relatedness (2023)
We have studied Wiwa/Sanja Amerindians HLA-A, -B, -C, -DRB1 and DQB1 allele frequencies and extended haplotypes in 52 unrelated individuals from “El Encanto” town at Guanachaca riverside. High frequency alleles were in general present in other Amerindian populations. Also, three extended haplotypes and eight ones were respectively both “new found” and already described in Amerindians from North, Central and South America, including Lakota-Sioux, Mayas, Teeneks, Quechua and Aymaras. Analyses of HLA-A*24:02 and -C*01:02 Wiwa high frequency alleles suggested a specific relatedness with another Amerindian and Pacific Islander ethnic groups (these two particular alleles bearing in high frequencies); they include New Zealand Maoris, Taiwanese, Japanese, Papua New Guinea, and Samoans among others. This may indicate that selective forces are maintaining these two alleles high frequency within this wide American/Pacific area. © 2018